Activity Potential of the Category “Ignorance” in Epistemological Space of the Educational Paradigm - I. N. Charikova; S. M. Kargapoltsev; E. V. Likhnenko (Высшее образование в России)
Modern justifications of essential interrelation and interdependence between the concepts of “knowledge” and “ignorance” in many ways can contribute to theoretical, methodological, and practical specification of forms and means of pedagogical mediation of the process of personal development of a subject of knowledge. The category of “ignorance” is inextricably linked with getting, “extraction” of a new knowledge in a problem subject sphere in the process of problem analysis and search for solutions.The purpose of the article is a consideration of conceptual grounds for knowledge formation using the activity potential of the category of “ignorance”. The activity approach became a methodological framework for the study aimed at the improvement of cognitive processes, transformation of knowledge into the potential of person’s self-development within the epistemological space of the educational paradigm.